5-Fluorouracil, Leucovorin, Oxaliplatin, and Irinotecan as a Potential Standard for Second-line Therapy in Extrapulmonary Neuroendocrine Carcinomas - Ho, I-Wei; Chiang, Nai-Jung; Lai, Jiun-I; Chang, Peter Mu-Hsin; Chen, San-Chi; Hung, Yi-Ping; Chen, Ming-Huang (Journal of cancer research and practice, 2024)
Abstract Background: Neuroendocrine carcinomas (NECs) are classified by the World Health Organization as poorly differentiated, aggressive Grade 3 tumors with high proliferative indices and frequent lung involvement. While initial treatment for advanced NEC typically involves etoposide and platinum-based therapies, standardized options for subsequent lines of treatment are lacking. This study evaluates the efficacy and outcomes of various second-line treatments for NECs following progression after initial therapy. Materials and Methods: A retrospective cohort study was conducted at Taipei Veterans General Hospital, Taiwan, from January 2016 to June 2023. The study included patients aged 18 years or older diagnosed with extrapulmonary NEC who had progressed following initial platinum and etoposide therapy. Treatment response and survival outcomes were assessed. Results: The study analyzed 34 patients across four treatment regimens: 5-fluorouracil, leucovorin, oxaliplatin, and irinotecan (FOLFOXIRI), 5-fluorouracil, leucovorin, and irinotecan, 5-fluorouracil, leucovorin, and Nivolumab + Ipilimumab. The FOLFOXIRI regimen demonstrated the highest objective response rate of 33.3% and a disease control rate of 66.7%, compared to the other groups, with a median progression-free survival of 4.1 months and median overall survival of 9.7 months. Conclusion: The FOLFOXIRI regimen shows potential as an effective second-line treatment for patients with extrapulmonary NEC who have progressed after first-line therapy with platinum/etoposide.